Academic training and business entrepreneurship capacity of students in a Faculty of Administrative Sciences - Alarcón Cerna, Jorge Luis (2022)
The present research work focused on the analysis of university academic training in the Faculty of Administrative Sciences from the Major National University of San Marcos, and how it influences the business entrepreneurship capacity of students, from the third to the tenth cycle, the study was based on the population that amounts to 1632 students with a sample of 315 students, a data collection instrument was developed, which was previously validated with a good rating, this research responds to the research hypothesis, where concludes that there is a significant link between the study variables, establishing the capacity for business entrepreneurship as a dependent variable and the academic training variable as an independent variable, the approach is quantitative, the research is of a causal correlational descriptive type, it is based on a hypothesis that you want to contrast. Finally, recommendations are presented for teachers and students to follow.